2018
DOI: 10.1105/tpc.17.00911
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar H+-Pyrophosphatase and Cytosolic Soluble Pyrophosphatases Cooperatively Regulate Pyrophosphate Levels in Arabidopsis thaliana

Abstract: Inorganic pyrophosphate (PPi) is a phosphate donor and energy source. Many metabolic reactions that generate PPi are suppressed by high levels of PPi. Here, we investigated how proper levels of cytosolic PPi are maintained, focusing on soluble pyrophosphatases (AtPPa1 to AtPPa5; hereafter PPa1 to PPa5) and vacuolar H-pyrophosphatase (H-PPase, AtVHP1/FUGU5) in In planta, five PPa isozymes tagged with GFP were detected in the cytosol and nuclei. Immunochemical analyses revealed a high abundance of PPa1 and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 66 publications
4
53
0
Order By: Relevance
“…The tissue width increased over time in the WT but remained constant in the an-1 fugu5-1 double mutant. Segami et al, 2018). Indeed, the H + -PPase loss-of-function fugu5 mutants of Arabidopsis exhibit a pleiotropic phenotype, as they fail to reactivate cell cycling in cotyledonary palisade tissue following seed imbibition due to inhibition of gluconeogenesis from seed-stored TAG (Ferjani et al, 2011).…”
Section: The Pleiotropic Yet Specific Targets Of Ppi In Arabidopsismentioning
confidence: 99%
See 3 more Smart Citations
“…The tissue width increased over time in the WT but remained constant in the an-1 fugu5-1 double mutant. Segami et al, 2018). Indeed, the H + -PPase loss-of-function fugu5 mutants of Arabidopsis exhibit a pleiotropic phenotype, as they fail to reactivate cell cycling in cotyledonary palisade tissue following seed imbibition due to inhibition of gluconeogenesis from seed-stored TAG (Ferjani et al, 2011).…”
Section: The Pleiotropic Yet Specific Targets Of Ppi In Arabidopsismentioning
confidence: 99%
“…Therefore, PPi exerts an inhibitory effect on specific targets within different cell types. In other words, the function of H + -PPase, the major PPi-hydrolyzing enzyme in plant cells (Ferjani et al, 2014;Segami et al, 2018), goes beyond housekeeping, and the breadth and specificity of its contribution warrants investigation.…”
Section: The Pleiotropic Yet Specific Targets Of Ppi In Arabidopsismentioning
confidence: 99%
See 2 more Smart Citations
“…Various proton (H + )‐pumps with different functions are known to localize in specific cellular components (Serrano, ; Segami et al , ). In this study, we analyzed TaVP subcellular location through a transient expression approach and showed that the TaVP‐GFP fusion is localized in the tonoplast (Fig.…”
Section: Discussionmentioning
confidence: 99%